2019
DOI: 10.1002/jcb.28875
|View full text |Cite
|
Sign up to set email alerts
|

Feedback modulation of endothelial cells promotes epithelial‐mesenchymal transition and metastasis of osteosarcoma cells by Von Willebrand Factor release

Abstract: Endothelial cells (ECs), as a tumor niche cell, generate and secrete Von Willebrand factor (VWF) that is linked to osteosarcoma (OS) progression. However, the role and regulatory mechanisms of VWF that underpin OS progression remain unclear. Here, using a coculture system ex vivo, we showed that ECs promoted the epithelial‐mesenchymal transition (EMT) process in OS cells via enhanced VWF secretion. VWF secreted by ECs directly contributed to OS EMT and metastasis by activating NF‐κB signaling. In addition, OS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Recent studies by Liu et al confirmed that EMT activation can increase the invasion and metastasis ability of osteosarcoma cells, and promote the progression of osteosarcoma [27,28]. The main features of EMT activation include down-regulation of epithelial cell markers such as E-cadherin, and increased expression of mesenchymal phenotypic markers such as Vimentin and N-cadherin [29,30]. Our study found that after PRR11 was downregulated, the invasion and migration ability of osteosarcoma cells U2OS was significantly reduced.…”
Section: Discussionsupporting
confidence: 68%
“…Recent studies by Liu et al confirmed that EMT activation can increase the invasion and metastasis ability of osteosarcoma cells, and promote the progression of osteosarcoma [27,28]. The main features of EMT activation include down-regulation of epithelial cell markers such as E-cadherin, and increased expression of mesenchymal phenotypic markers such as Vimentin and N-cadherin [29,30]. Our study found that after PRR11 was downregulated, the invasion and migration ability of osteosarcoma cells U2OS was significantly reduced.…”
Section: Discussionsupporting
confidence: 68%
“…VWF may also promote the transformation of tumor cells to facilitate metastasis as well. For instance, VWF released by endothelial cells, when co-cultured with osteosarcoma cells, induces the osteosarcoma cells to undergo epithelial mesenchymal transitioning, which is an essential step in tumor metastasis [ 118 ].…”
Section: Vwf Adamts13 and Cancer Metastasis Riskmentioning
confidence: 99%
“…Cancer cells promote the secretion of WPBs and vWF from ECs (237,238) and elevated plasmatic vWF correlate with tumor grade and metastasis (239). Moreover, vWF secretion has been reported to contribute to the process of EMT (240), the secretion of pro-inflammatory cytokines, and vascular permeability (234). Several studies show vWFdependent cancer cell adhesion to the endothelium is mediated by integrin receptors and facilitates extravasation during metastasis (239,(241)(242)(243).…”
Section: Coagulation Cascade and Autophagy In The Tumor Endotheliummentioning
confidence: 99%